Playing Games: A Cross-Sectional Study of Food Recall, Sleep Quality, and Physical Activity in Women Aged 18-22 Years Actively Playing Games - Ramadan, Gilang; Samin, Giofandi (Universitas Muhammadiyah Kuningan, 2023)
This research explores how women aged 18-22 play video games and their gaming habits regarding nutritional intake, sleeping habits, and daily physical activity while playing video games. The research method used is quantitative research with a cross-sectional research design. Data collection is carried out by collecting exposure and results simultaneously to describe the subject's characteristics and the relationship between variables. The research results were that video game players did not adopt a healthy lifestyle due to poor physical activity, poor diet, consuming relatively large amounts of caffeine while playing video games, and poor sleep quality. Conclusion: Everyone who plays video games must also pay attention to their health to live an everyday life as usual.